Proses Morfologis Gairaigo pada Game Kantai Collection - Jagadhita, Raditya; Kadir, Puspa Mirani; Wagiati (AYUMI : Jurnal Budaya, Bahasa dan Sastra, 2023)
The game Kantai Collection, more commonly known as Kancolle, is a Japanese-language game that is very popular among young Japanese people, especially among fans of anime-themed games. This game is set in the background of World War II and features many foreign characters who use gairaigo (loanwords from foreign languages) in their conversations. Gairaigo refers to borrowed words from foreign languages used by the Japanese people. The aim of this research is to classify the morphological processes of gairaigo in the source data and analyze how these gairaigo words are formed. This study is a qualitative descriptive research using the free observation method. The research collected data from six characters who frequently use gairaigo. The results of the study found 57 gairaigo words, consisting of 48 affixations, 6 combinations, and 3 word truncations, but no reduplication or direct borrowing was found. Furthermore, there were no changes in word classes in these gairaigo affixations. Keywords: gairaigo; game; morphological process.